ETHNOMATHEMATICS-PROBLEM BASED LEARNING IN THE “BALOY ADAT TIDUNG” CONTEXT: EFFECTS ON STUDENTS’ MATHEMATICAL CREATIVITY AND GROWTH MINDSET - Sury Adellia Ramadhanta; Marsigit Marsigit (Universitas Labuhanbatu, 2026)
Purpose – This study aimed to examine the effectiveness of Ethnomathematics-based Problem-Based Learning (PBL) and Ethnomathematics-based Student Teams Achievement Division (STAD) in enhancing students' Mathematical Creative Thinking Ability (MCTA) and Growth Mindset (GM), and to determine which instructional model is more effectiveMethodology – A quasi-experimental, nonrandomized control-group pretest–posttest design was employed at a public junior secondary school in Indonesia during the 2025/2026 academic year. The sample consisted of two intact ninth-grade classes (32 students each) assigned to the PBL and STAD groups. Data were collected using a mathematical creative thinking test and a growth mindset questionnaire administered at pretest and posttest. Data analysis involved one-sample t-tests to assess the effectiveness of each learning model against the established effectiveness criteria; differences in effectiveness between groups were analyzed using a multivariate test (Hotelling's T²) to see the simultaneous effect on MCTA and GM, independent-samples t-tests to compare group differences, and a superiority analysis to identify the more effective approach.Findings – Both Ethnomathematics-based PBL and STAD were effective in improving students' MCTA and GM. However, the PBL model demonstrated significantly greater effectiveness than the STAD model in enhancing both variables.Contribution – This study provides empirical evidence supporting the integration of the ethnomathematical context